Klasifikasi Karakteristik Kepribadian Siswa Berdasarkan Tipologi Hippocrates-Galenus dengan Metode Decision Tree-C4.5 - Suliman, Suliman; Kusumawati, Nilam; Sahrullah, Sahrullah (Journal of Computer System and Informatics (JoSYC), 2024)
Problem behavior or personality in students this no simple problem, moreover _ problem behavior in students school medium above (SMA), where at the level of the is Step teenager going to mature, so change behavior will seen clear on yourself students. If behavior the no get proper handling and direction, behavior _ the will attached permanent on personality students. Then based on problem that, then will conducted implementation on test typology hippocrates-galenus with C4.5 decision tree method for knowing character personality students school medium top (high school). Based on the Hippocrates-Galenus Typology process with the Decision Tree C4.5 method, discussions and calculations obtained the percentage results and test results of training data have level score answer by 100% of the 100 data that was taken and resulted in a 20% error because of the training data no in accordance with testing system , then the tests carried out by the system use method Decision Tree C4.5 generates level success by 80% which is appropriate with training data.